Empirical Analysis and Agent-Based Modeling of the Lithuanian Parliamentary Elections - Aleksejus Kononovicius (Complexity)
We analyze a parties’ vote share distribution across the polling stations during the Lithuanian parliamentary elections of 1992, 2008, and 2012. We find that the distribution is rather well fitted by the Beta distribution. To reproduce this empirical observation, we propose a simple multistate agent-based model of the voting behavior. In the proposed model, agents change the party they vote for either idiosyncratically or due to a linear recruitment mechanism. We use the model to reproduce the vote share distribution observed during the election of 1992. We discuss model extensions needed to reproduce the vote share distribution observed during the other elections.